ОЧЕКУВАНОTO ТРАЕЊЕ НА ЖИВОТОТ ВО ЕВРОПСКИТЕ ЗЕМЈИ И НИВНАТА КОРЕЛАТИВНА ЗАВИСНОСТ СО БРУТО-ДОМАШНИОТ ПРОИЗВОД ПО ЖИТЕЛ (Yearbook - Faculty of Economics, 2018)
The Statistical data presents that life expectancy in Republic of Macedonia for 2005 in average, was recorded to 74 years, and in the EU countries it was 75 years in Poland and 82 years was recorded for Austria. While data processing there was established that the correlation coefﬁ cient ratio between average life expectancy in the EU countries and their GDP per capita is highly enough and it was 0,85 that means a strong correlation dependence, while determination coefﬁ cient ratio was calculated to 77% which means that, standard of living, presented through GDP has 77% inﬂ uence over life expectancy of population, and the rest of 23%  inﬂ uenced some other factors. This is a real truth because the better standard of living procures and more comfort living also, with a opportunity for more expenditures for better life of the people, i.e. (early detection of diseases, holidays, regular and healthy food etc.). In this paper are elaborated processed statistical data and relevant comments to it through an table and graphic presentation.